Proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction 2014
DOI: 10.1145/2559636.2559681
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method approach to evoke creative and holistic thinking about robots in a home environment

Abstract: Discovering older adults' perceptions and expectations of domestic care service robots are vital in informing the design and development of new technologies to ensure acceptability and usability. This paper identifies issues that were elicited from older adults using different methods to promote creative thinking about domestic robots at an emotional level, as well as pragmatic level. These included exploring people's ideal embodiment preferences and requirements for a domestic care service robot, and also wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Researchers have explored independently living older adults' opinions of using a robot in the home and preferences for assistance from robots vs. humans for household maintenance [4]. Some research has found that older adults wish robots to provide social interaction in addition to functional assistance such as home upkeep [3,10], though other research has found that older adults are not particularly interested in companionship from robots [8].…”
Section: Older Adults' Involvement In Robotics Researchmentioning
confidence: 99%
“…Researchers have explored independently living older adults' opinions of using a robot in the home and preferences for assistance from robots vs. humans for household maintenance [4]. Some research has found that older adults wish robots to provide social interaction in addition to functional assistance such as home upkeep [3,10], though other research has found that older adults are not particularly interested in companionship from robots [8].…”
Section: Older Adults' Involvement In Robotics Researchmentioning
confidence: 99%
“…Due to the lack of existing research in collaboratively designing robot algorithms, we developed our collaborative research methodologies through a negotiation process with participants. A growing number of robot design research investigates how to adopt participatory design methodologies to co-design the appearance of robots and their interaction behaviors [10,14,48,53,56]. However, robot algorithms are black-boxed, and novice research participants have limited knowledge about algorithm development processes [83].…”
Section: Collaborative Research Methodologymentioning
confidence: 99%
“…Being able to give commands to the robot could go beyond direct commands and allow the user to indicate needs and preferences. Some older adults have expressed the desire to be able to specify to the robot what they want it to do or not do [8], thereby restricting the robot's autonomy to advance the user's autonomy.…”
Section: Needs Of Older Adultsmentioning
confidence: 99%